Spatio-Temporal Analysis on Land Use/Land Cover Change in Banda Aceh: A Preliminary Study of Disaster Resilience - Senjana, Suci; Handayani, Wiwandari; Suprapti, Atik (IOP conference series. Earth and environmental science, 2023)
The devastating tsunami that struck Banda Aceh resulted in profound destruction to both its built environment and natural areas. The city’s urban infrastructure suffered extensive damage, with essential zone being severely affected. Despite these challenges, the population of this tsunami-prone city has continued to increase steadily over time. This research examines the land use/land cover (LULC) in Banda Aceh following the 2004 Indian Ocean Tsunami through spatio-temporal analysis, with a particular focus on investigating urban growth trends through the examination of built-up areas. The study seeks to discern the evolving patterns of land use and land cover transitions over this period, shedding light on the transformative processes associated with urbanization and its consequent impact on the landscape. The insights obtained from this research can inform urban planners, policymakers, and disaster management authorities in devising effective strategies for urban growth in coastal front cities that vulnerable to tsunami.